Predictive factors of death associated with infective endocarditis in adult patients with congenital heart disease. Issue 3 (28th January 2020) - Ly, Reaksmei; Compain, Fabrice; Gaye, Bamba; Pontnau, Florence; Bouchard, Melissa; Mainardi, Jean-Luc; Iserin, Laurence; Lebeaux, David; Ladouceur, Magalie
Abstract: Aims: Infective endocarditis is a severe infection which can occur in adult patients with congenital heart disease. We aimed to determine outcomes and risk factors of death in adult congenital heart disease and to investigate differences with infective endocarditis in non-congenital heart disease. Methods and results: Between March 2000 and June 2018, 671 consecutive episodes of infective endocarditis in adult patients were retrospectively recorded. Cases were classified according to the modified Duke classification. All adult congenital heart disease cases were managed by infectious disease specialists and adult congenital heart disease cardiologists. During this period, 142 infective endocarditis episodes (21%) occurred in adult congenital heart disease patients with simple (46.5%), moderate (21.1%), or complex (32.4%) congenital heart disease. In-hospital mortality was 12.7%. The strongest predictive factors of in-hospital death in multivariate analysis were complexity of congenital heart disease (odds ratio (OR) 8.02, 95% confidence interval (CI) 1.53–42.07), age (OR 1.05, 95% CI 1.00–1.19) and white blood cell count 12 g/L or greater (OR 8.72, 95% CI 2.42–31.43). Patients with congenital heart disease were significantly younger (median age 36 vs. 67 years, P <0.001), had undergone more redo cardiac surgeries (35.7% vs. 11.3%, P <0.01) and presented with more right-sided infective endocarditis (39.4% vs. 7.9%, P <0.01) than patients without congenital heart disease. Congenital heart disease was associated with two-fold lower in-hospital mortality rates (OR 0.37, 95% CI 0.19–0.74), independently of age, gender, obesity, renal function and side of infective endocarditis. Conclusion: Although mortality associated with infective endocarditis is lower in adult patients with congenital heart disease than patients without congenital heart disease, infective endocarditis mortality is particularly high in patients with complex congenital heart disease. Education and prevention about the risk of infective endocarditis is essential, especially in this group.